Wood Protection and Preservation - Brischke, Christian (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Wood is an advantageous building material in many respects, but it is biodegradable and therefore requires protection when used in highly hazardous applications. This Special Issue comprises 19 papers by authors from 14 countries in Asia, North America and Europe. They represent a wide range of aspects related to wood protection and wood preservation, and give timely examples of research activities that can be observed around the globe. Several authors reported on the processes of thermal modification and different chemical wood modification techniques, which are among the latest alternative wood protection methods without the use of biocides. New preservatives and assessment methods of preservative-treated wood products are presented, as well as studies on the natural durability of wood, fire-retardant treated wood, the effect of concrete on wood durability and different novel surface modification techniques using plasma. In addition to biological durability, the mechanical properties, moisture performance, bonding properties, weathering stability and the corrosiveness of differently treated wood are investigated and reported within this Special Issue. Examples of research on fungal biology, service life planning with wood and test methodology are also included and complete the Special Issue.